Electro-chemo-mechanics of lithium in solid state lithium metal batteries. Issue 2 (17th December 2020) - Tang, Yongfu; Zhang, Liqiang; Chen, Jingzhao; Sun, Haiming; Yang, Tingting; Liu, Qiunan; Huang, Qiao; Zhu, Ting; Huang, Jianyu
Abstract : This review summarizes the impact of the electro-chemo-mechanics of lithium on dendrites and interfaces in solid state lithium metal batteries. Abstract : Using lithium as the anode material to achieve high energy density lithium-ion/metal batteries is the ultimate goal of energy storage technology. A recent development of solid state electrolytes (SSEs) with high ionic conductivity holds great promise for enabling the practical applications of solid state lithium metal batteries (SSLMBs), as the high mechanical strength of SSEs can be harnessed to suppress dendrite growth. However, the application of SSLMBs is hampered by the new multifold problems from the solid–solid contact to dendrites to deleterious interfacial reactions between lithium and the SSEs. In this burgeoning field of SSLMBs, it is imperative to understand the fundamental science of these emerging problems at a very basic level before the application of SSLMBs can be realized. These problems are inter-related and they arise from the intrinsic physical, chemical, and electro-chemo-mechanical properties of lithium. We start this review by providing a brief account of the history of lithium, and how it has evolved from the anode of primary lithium metal batteries to that of liquid electrolyte based rechargeable batteries and to that of SSE based SSLMBs. We then summarize the literature about the mechanical properties of bulk lithium, lithium pillars and lithium whiskers. We analyze from an electro-chemo-mechanical perspective how lithium dendrites penetrate through SSEs and cause short circuits in SSLMBs. We identify possible strategies to mitigate lithium dendrite propagation through SSEs, and summarize our understanding of the lithium reaction with various interfaces, such as Li/Li7 La3 Zr2 O12, Li/polyethylene oxide, Li/Na-superionic conductor, and Li/sulfide, with the ultimate goal of developing strategies to mitigate detrimental interfacial reactions and maintain sustainable stable interfaces. We review briefly characterization tools to address the challenging issues in SSLMBs. We conclude by pointing out the outstanding issues in SSLMBs.